Intensifying inequality? Gendered trends in commercializing and diversifying smallholder farming systems in East Africa - Tavenner, Katie; Wijk, Mark T. van; Fraval, Simon; Hammond, James; Baltenweck, Isabelle; Teufel, Nils; Kihoro, Esther; Haan, Nicoline C. de; Etten, Jacob van; Steinke, J.; Baines, D.; Carpena, Pietro; et al. (Frontiers Media, 2019)
While the commercialization and diversification of agricultural and livestock systems have been identified as key global strategies for climate change adaptation and mitigation, less is known as to the large-scale gendered impacts that are implicated in these transformations among smallholder crop and livestock farmers. This study explores these gender impacts across different farming systems and gender-respondent-household typologies using data from the Rural Household Multiple Indicator Survey (RHoMIS) in 2,859 households in three East African countries—Ethiopia, Kenya, and Tanzania. Female control scores over incomes or foodstuffs produced through both on and off farm activities were highest in farming systems that had more land and more livestock. However, increasing commercialization—defined herein as the increasing importance of crop and livestock sales to farm households—resulted in an overall decline in female control across all farming systems and gender-respondent-household typologies. In contrast, crop and livestock diversification were positively associated with female control across gender-respondent-household typologies. Analysis of specific crops and livestock products across farming systems and respondent typologies revealed women have far greater control over decisions related to consumption than decisions related to sales, although the gap between the two were less pronounced in lesser-valued livestock products (chickens, eggs). However, the analyses suggest that as sale of crops and livestock increase, female control over these areas could likely diminish, regardless of specific activity. The authors conclude that approaches to adapt to or mitigate climate change that rely on increasing market orientation of smallholder production will likely intensify men's control over benefits from production, whereas diversification will likely have a more positive impact on female control. Thus, climate adaptation strategies promoting increased diversification will likely have a more positive impact on women smallholders than commercialization alone. The authors recommend that when commercialization is the target intervention, it must be accompanied by a gender differentiated analysis of trade-offs and risks to mitigate the potential negative consequences shown in this study.